Management of Quality Improvement of Graduates of Professional Teacher Education - Fauyan, Muchamad; Majid, Abdul; Rif’iyati, Dian; Abdul Majid (Universitas Pendidikan Ganesha, 2025)
The Teacher Professional Education (PPG) Program faces challenges in improving the quality of graduates to ensure their relevance to the world of education. This situation results in PPG graduates not being fully prepared to face various dynamics in the school environment. Based on this, the purpose of this study is to analyze the effectiveness of benchmarking and tracer studies in improving the quality of PPG graduates. This study used a mixed approach (qualitative and quantitative) with PPG administrators and alumni from 2021-2022 as subjects. Data collection methods used observation, questionnaires, interviews, and documentation studies. The data collection instrument used a questionnaire sheet. Data analysis techniques used thematic and descriptive analysis. The in-service PPG program showed a positive impact with an average score of 4.28 and a score of 85.54, categorized as